Learning mediated by the use of digital technologies in the teachers 'conception: a case study in the technical course in buildings of Federal Institute of Education, Science and Technology of the North of Minas Gerais - IFNMG/Campus Januária (Research, Society and Development, 2020)
Professional and Technological Education is inserted in the development of human skills in order to transform reality. Thus, we cannot fail to emphasize the potential of using digital technologies as mediating instruments in educational practices in this context of integral human formation. In this sense, this research aims to identify the teachers' conceptions of the technical course in Buildings of the Federal Institute of Education, Science and Technology of the North of Minas Gerais (IFNMG), campus Januária, about the use of digital technologies in educational practices for contribution of student learning, in the context of Professional and Technological Education (EPT) at the secondary level in the subsequent/concomitant modality. For this, it was elected an exploratory research, using the bibliographic survey and the case study as technical procedures. Data collection was performed with the application of a questionnaire and the qualitative analysis of the responses was made using the method of analysis by categories proposed by Bardin. In addition, it relied on the authors Ciavatta and Schiedeck to address integrated training at EPT, in Freire, Vygotsky and Kenski for the use of mobile devices in mediation for learning from the perspective of training for autonomy.